Recent advances in the asymmetric phosphoric acid-catalyzed synthesis of axially chiral compounds - Woldegiorgis, Alemayehu Gashaw; Lin, Xufeng (Beilstein Journal of Organic Chemistry, 2021)
In recent years, the synthesis of axially chiral compounds has received considerable attention due to their extensive application as biologically active compounds in medicinal chemistry and as chiral ligands in asymmetric catalysis. Chiral phosphoric acids are recognized as efficient organocatalysts for a variety of enantioselective transformations. In this review, we summarize the recent development of chiral phosphoric acid-catalyzed synthesis of a wide range of axially chiral biaryls, heterobiaryls, vinylarenes, N-arylamines, spiranes, and allenes with high efficiency and excellent stereoselectivity.
Keywords: allenes; atropisomerism; axial chirality; chiral phosphoric acid; heterobiaryls; spiranes